Belize : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Excutive Director for Belize. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This 2016 Article IV Consultation highlights that the economy of Belize is facing multiple challenges. GDP growth slowed to 1 percent in 2015 owing to falling oil production and reduced output in the primary commodity sectors, and turned to negative 1.5 percent in the first half of 2016 relative to the same period in 2015. The decline in oil and other commodity prices led to deflation in 2015. GDP is projected to decline by 1.5 percent in 2016. The current account deficit would slowly improve owing to a gradual recovery in major commodity exports, but would remain high, indicating a weak external position.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet